Battery certification for space prototype applications (2014)
ABSTRACT: Night Vision experiment, on Endeavour’s STS-134 mission, consisted on exposing micro-algae, with cellular organelles similar to human retina, to space conditions. The experiment required the development of a nonrechargeable battery-powered instrument for biological material life support. Crew and ship safety is vital in space flight; thus, the experiment’s use of batteries must be certified through a series of technical tests required by NASA. This article describes the certification process, including: the protection of circuits, and the electrical, vibration and vacuum tests. Finally, test results, that allowed the use of the instrument in space, are shown.